Fundamentals of Robotic Mechanical Systems Theory, Methods, and Algorithms - Angeles, Jorge (Mechanical Engineering Series, 2014)
The 4th edition includes updated and additional examples and exercises on the core fundamental concepts of mechanics, robots, and kinematics of serial robots. New images of CAD models and physical robots help to motivate concepts being introduced. Each chapter of the book can be read independetly of others as it addresses a seperate issue in robotics.